IMPACT OF NATURAL AND ANTHROPOGENIC RADIOACTIVE SOURCES ON POLLUTION OF THE ENVIRONMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
Radioactivity, as a process of spontaneous decay of atomic nuclei, the energy is being released through alpha, beta and gamma radiation, which affect both the environment and human beings. Studies show that technogenic radioactive objects' negative impact on the human body is less, than some natural phenomena have.
Keywords: radioactivity; exposure; emanation; cancer; building materials